Optimal Light Source Intensity Setting in Endoscopic Ear Surgery. Issue 2 (30th November 2021) - Vachutka, Jaromir; Trneckova, Marketa; Salzman, Richard; Kolarova, Hana; Belakova, Petra
Abstract : Hypothesis: Higher light intensity settings do not yield improved image quality in endoscopic ear surgery. Background: Light intensity is a parameter with major impact on the quality of digital images. For ear surgery, light produces heat associated with a thermal risk to ear structures and the light source setting should be accordingly optimized. Methods: Several series of still images were acquired during live middle ear surgery, using cadaveric and plastic temporal bone models and with three-dimensional printed models. Images obtained under varying light intensities were compared with the image acquired at maximum intensity of a light emitting diode light source. We analyzed digital image brightness and noise using quantitative methods. Results: Our measurements revealed significantly decreased image brightness with light intensities set below 20% with an increase in noise at light intensities lower than 30%. Conclusion: The optimal light source setting corresponded to 30% intensity in our experimental set-up. Special attention should be given to those cases where faster image quality degradation is expected (dark or bloody scenes or larger cavities). The results were strongly dependent on the equipment used. The methods described in this study can serve as a general guide for determining the optimal light source setting in any specific set-up.